2021
DOI: 10.1111/joss.12732
|View full text |Cite
|
Sign up to set email alerts
|

Study of consumer perception about low‐sodium foods and characteristics related to perception and purchase of low‐sodium spreadable processed cheese

Abstract: This study interviewed 1,511 consumers using an online questionnaire to understand consumer behavior on reduced-sodium products and the buying interest for processed cheese with low sodium content. Likert scale techniques were applied, which was assessed by analyzing factors (49.38%), Cronbach's alpha (0.694) and KMO (0.703), which conferred reliability to the applied test, and word association and completion task, which were evaluated chi-square and chi-square per cell, respectively showing X 2 = 799,635 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…From this, cured dried meat could be considered if safety in the products is prioritized. However, the demands of the market might lean toward lower sodium contents in dried meat as consumers nowadays are more aware of the health benefits of low sodium diets ( 158 ). Nevertheless, it was said that neither of the curing ingredients could effectively increase pathogen lethality by themselves ( 151 ).…”
Section: Safety and Challenges Of Dried Meats And How To Prevent Themmentioning
confidence: 99%
“…From this, cured dried meat could be considered if safety in the products is prioritized. However, the demands of the market might lean toward lower sodium contents in dried meat as consumers nowadays are more aware of the health benefits of low sodium diets ( 158 ). Nevertheless, it was said that neither of the curing ingredients could effectively increase pathogen lethality by themselves ( 151 ).…”
Section: Safety and Challenges Of Dried Meats And How To Prevent Themmentioning
confidence: 99%
“…Studies have shown that consumers are interested in sodium‐reduced food items and that food items that had slight to moderate sodium reduction were well accepted by consumers (Hoppu et al ., 2017; Park et al ., 2020; de Melo et al ., 2022; Vinitha et al ., 2022), but this consumer liking of sodium‐reduced products highly varies depending on the type of food item. For example, reduced sodium bread and processed meat products received higher consumer liking scores due to interactions of other taste compounds such as spices, sugar and fats to mask the salt reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Different research methods have been used to investigate what consumers feel and think (de Andrade, de Sobral, Ares, & Deliza, 2016; Gambaro, 2018; Popoola, Anders, Feuereisen, Savarese, & Wismer, 2021). Assessing consumer perception is a technique used to identify the factors that influence on the purchase and consumption of certain foods (de Melo et al, 2022), as well as to better understand consumer behavior based on their consumption habits (Penna et al, 2022; Viana et al, 2021). This information helps to determine the potential of certain products in a growing market.…”
Section: Introductionmentioning
confidence: 99%